European Society of Hypertension position paper on renal denervation 2018. Issue 10 (October 2018) - Schmieder, Roland E.; Mahfoud, Felix; Azizi, Michel; Pathak, Atul; Dimitriadis, Kyriakos; Kroon, Abraham A.; Ott, Christian; Scalise, Filippo; Mancia, Giuseppe; Tsioufis, Costas
Abstract : N/A: This ESH update was deemed necessary with the publication of new results of sham-controlled randomized blinded prospective trials with renal denervation (RDN). Proof of concept studies and first randomized trials (some were sham-controlled) displayed discrepant results about the efficacy of RDN. Three sham-controlled randomized trials of the 2.0 generation yielded now similarity in the average blood pressure decrease following RDN. Reduction of ambulatory blood pressure was approximately 5 to 7 mmHg and of office blood pressure 10 mmHg. Such a decrease in blood pressure by pharmacologic therapy has been found to be associated with lower incidence of cardiovascular events in particular with respect to heart failure and stroke by roughly 25%. Nevertheless, some questions about renal denervation are unanswered. The heterogeneity of the blood pressure-lowering response point to the clinical need to identify predictors for efficacy, and questions on long-term safety could not have been answered due to the short duration of the sham-controlled randomized clinical trials.